Identifying the dominant electrochemical reaction in electrochemical impedance spectroscopy. (20th December 2021) - Moradighadi, Negar; Nesic, Srdjan; Tribollet, Bernard
Abstract: Electrochemical Impedance Spectroscopy (EIS) is frequently used for the study of electrochemical reactions and associated mechanisms and phenomena. To study a specific reaction, it is important to choose the DC potential at which the measured impedance data carries information mostly related to that specific reaction. One of the first questions asked was: at different potentials, which reaction contributes most to the recorded impedance spectra, cathodic or anodic? For example, at the corrosion potential where the cathodic current density is equal to the anodic current density, does the impedance data carry information about the two reactions equally? The following study is the development of a methodology that is essential as the first step for analysis of the impedance data related to an electrochemical reaction. This methodology consists of a new model that predicts which reaction is dominant to the measured impedance at any specific potential. The experimental results provided confirm the validity of the model.